DNA repair kinetic of hydrogen peroxide and UVA/B induced lesions in peripheral blood leucocytes from xeroderma pigmentosum patients and healthy subjects - Prieto Gonzalez, Elio A. (2014)
The objective of the present work was to study the fine kinetics of DNA repair in xeroderma pigmentosum (XP) syndrome, a complex disorder linked to a deficiency in repair that increases cancer susceptibility. The repair process was evaluated by the comet assay (CA) in cells from 2 XP patients and 9 controls exposed to UVA/B (UVA 366/UVB 280 nm) and H2 O2 (150 µM) at temperatures of 4, 15, and 37°C. Samples were taken at 2-min intervals during the first 10 min to analyze the “fine kinetics” repair during the initial phase of the curve, and then at 15, 20, 25, 30, 45, 60, and 120 min. CA evaluation of DNA repair activity points to BER/NER initiation in the first 30 min with both inductors at 37°C and 15°C, but final comet length showed differences according to treatment. Repair kinetics during 120 min showed a good correlation with clinical features in both XP patients. Differences in final comet length were less pronounced in XP cells treated with H2 O2 than with UVA/B, probably because the peroxide produces mainly base oxidation but less bulky lesions; UVA/B generates a mixture of both. These findings reinforce the value of CA in testing in DNA repair ability or exposure monitoring